Get x on one side then you can use substitution
So, change x+3y=3 to x= -3y+3
Then plug in x to other equation to find y
2(-3y +3)-3y=-12
-6y + 6 -3y = -12
-9y = -18
Divide both sides by negative nine to find y
y = 2
Then plug in to original equation to find x
x + 3(2) = 3
x + 6 = 3
x = -3
So, y = 2 and x = -3
Answer:
so first convert to fraction so
9 3/4 = 39/4
so it was spread among 3
so this is division so you do 39/4 divided by 3
so you keep switch flip
which is 39/4 *1/3
answer is 13/4
Answer:
-3
Step-by-step explanation:
5+-3 equals 2 because it is technically 5-3.
Answer:
$8-$6+$8-$3=$7
hope this helps have a good day or night:)
set is the collection of well defined object having some common property
please fOllow me